Digital Assessment Instrument for Science Education Courses in Teacher Training Programs - Rohmani; Berta Apriza; Yasinta Mahendra; Yuni Dwi Astuti (LPPM Undiksha, 2026)
The inefficiency and lack of objectivity of conventional assessment in large higher education classes, especially in teacher education, are problematic. Furthermore, the limited evaluation instruments capable of measuring in-depth conceptual understanding of technology remain a challenge that has not been adequately addressed. This study aims to develop, validate, and evaluate the feasibility of the SmartSains digital assessment instrument to improve the effectiveness, objectivity, and efficiency of science learning evaluation for students. The research used is Research and Development (R&D), using a systematically modified Borg and Gall model. The research subjects consisted of two experts as validators and 20 sixth-semester students as limited trial subjects. Data collection methods included expert validation sheets, the SmartSains platform for collecting student response data, and a Likert-scale practicality questionnaire. Data analysis used Aiken's V to test content validity, Cronbach's Alpha for reliability, and descriptive analysis to assess product practicality. The results showed that the SmartSains instrument had a very high level of validity and was considered very practical by students, with an average score of 4.45. Thus, it can be concluded that SmartSains is a digital assessment instrument that is feasible, effective, and capable of addressing learning evaluation problems in large classes. The implications of this study indicate that the use of technology-based digital assessment can improve the quality of learning evaluation, both in terms of efficiency, objectivity, and the student learning experience, and has the potential to serve as a model for developing evaluation instruments in other higher education contexts.